Foundation Rules: Establishing Ideal Concepts in Foundation Laws - Agus Nurudin (Amanna Gappa, 2020)
As welfare state, Indonesia is obliged to meet the basic social and economic needs of every citizen in order to guarantee a minimum standard of living. Inclusive welfare development is based on pro-ductivism, universal social investment and democratic governance. This article was conducted using library research with statute, comparative, and conceptual approaches. Meanwhile, data were analyzed descriptively, consisting of quotes. The results show that the foundation organs can be divided into three parts, namely the trustee, management and supervisor. Foundation as a legal entity has a distinctive character. This type of legal entity was born because of a legal act that is the separation of a number of wealth from the founder with a specific purpose. Limitation of the foundation as a legal entity may include several things, namely: the foundation as a legal entity, the wealth separated by the purpose of founding the foundation, does not have members, the founding of the foundation and the articles of association. Finally, it is appropriate that the Foundation Law to be reconstructed (building ideal concept) by including the roles, functions, responsibilities, obligations, and rights of the founders to avoid conflicts that might occur in the future.